Peningkatan Motorik Halus Anak Melalui Pembuatan Media Daur Ulang di Lingkungan Sekolah - Mila Ummu Walidatul Hamidah; Siti Rahmany Aprilina (Universitas Trunojoyo Madura, 2016)
This study aims to improve fine motor through the manufacture of recycled media. This research was conducted in kindergarten PKK Pandan in group B, some 10 children. This study uses a Class Action Research (PTK) with Kurt Lewin's design consists of two cycles, each cycle consisting of three meetings. Data analysis in this research is to describe changes in action through the medium of recycled materials in repairing and improving the fine motor skills of children in group B. Analysis of the data used in the research is the analysis of reflection based on the cycles. From the analysis, it was found that fine motor activities through coloring, cutting and sticking very well. This can be evidenced an increase in the first cycle and the second cycle.